Remote dance teaching at the Escola Livre de Dança da Maré in 2020 during the COVID-19 outbreak (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This paper attempted to reflect upon remote dance teaching experiences developed during the COVID-19 outbreak, in the city of Rio de Janeiro, in 2020, by the Escola Livre de Dança da Maré. Working with non-formal education in dance, through synchronous and asynchronous strategies, the school kept reaching out to its students the during social isolation imposed by the new coronavirus pandemic. In a context where social inequalities became even more evident for those who needed to be connected to the internet and use electronical devices to study at home, this paper reflected upon how the reality of the neighborhood of Maré did not cope with the best development of the online classes at the Escola Livre de Dança da Maré.
Keywords: Dance; Non-formal education; Remote teaching; COVID-19; Escola Livre de Dança da Maré